Perceptual Cue Weighting Is Influenced by the Listener's Gender and Subjective Evaluations of the Speaker: The Case of English Stop Voicing - Yu, Alan C. L. (Frontiers in Psychology, 2022)
Speech categories are defined by multiple acoustic dimensions and their boundaries are generally fuzzy and ambiguous in part because listeners often give differential weighting to these cue dimensions during phonetic categorization. This study explored how a listener's perception of a speaker's socio-indexical and personality characteristics influences the listener’s perceptual cue weighting. In a matched-guide study, three groups of listeners classified a series of gender-neutral /b/-/p/ continua that vary in VOT and F0 at the onset of the following vowel. Listeners were assigned to one of three prompt conditions (i.e., a visually male talker, a visually female talker, or audio-only) and rated the talker in terms of vocal (and facial, in the visual prompt conditions) gender prototypicality, attractiveness, friendliness, confidence, trustworthiness, and gayness. Male listeners and listeners who saw a male face showed less reliance on VOT compared to listeners in the other conditions. Listeners' visual evaluation of the talker also affected their weighting of VOT and F0 cues, although the effects of facial impressions differ depending on the gender of the listener. The results demonstrate that individual differences in perceptual cue weighting are modulated by the listener's gender and his/her subjective evaluation of the talker. These findings lend support for exemplar-based models of speech perception and production where socio-indexical features are encoded as a part of the episodic traces in the listeners' mental lexicon. This study also shed light on the relationship between individual variation in cue weighting and community-level sound change by demonstrating that VOT and onset F0 co-variation in North American English has acquired a certain degree of socio-indexical significance.